A Correlation between Chronic gastritis, Helicobacter pylori, Intestinal metaplasia and Atrophic change with Advanced Gastric Adenocarcinoma : a study in 139 Gastrectomy - Atisook, Kanit; Ruangjira-urai, Rujira (Siriraj Medical Journal, 2003)
Background : Atrophic gastritis with intestinal metaplasia is considered a precancerous lesion leading to intestinal type gastric adenocarcinoma. The current study aimed to describe the prevalence of gastric atrophy, intestinal metaplasia and H pylori infection in stomach with advanced gastric adenocarcinoma. Methods : One hundred and thirty-nine specimens of gastrectomy with the diagnosis of advanced gastric adenocarcinoma findings were reviewed for sits, location, size and macroscopic appearance of tumor. All section were reviewed for cancer type, degree of differentiation, and features of angiolymhatic invasion, perineurial invasion, depth of tumor invasion and lymph node metastasis. Sections were scored on a visual analogue scale to evaluation of chronic gastritis status, atrophic change, and intestinal metaplasia with subtype. Helicobacter pylori each location were identified. Results : Tumor was found more often in male than female with the ratio of 3:2 and predominantly in the age group of >=60 years old. No tumor was found in the age group of <30years. Most of the tumors were located in the posterior portion and lesser curvature of the antrum and the pylorus. Ulcerative type was found 65.9% followed by 15% of ulceroproliferative type, 15% of infiltrative type and 4% of fungating type. Adenocarcinoma was the common microscopic cell type (58.3%) followed by mixed adenocarcinoma and signet ring cell carcinoma 36.7% and pure signet ring cell carcinoma 5%. There was no statistically significant difference between cell types of tumor or cell differentiation with age group. More than 85% of tumor’s size was larger than 2 cm in diameter. Lymph node metastasis, angiolymphatic invasion and perineurial invasion were significantly found in tumor with larger than 2 cm in diameter. Ulcerative, ulceroproliferative infiltrative type had high incidences of angiolymhatic, perineurial invasion and lymph node metastasis comparing to fungating type. All microscopic cell carcinoma) had also high incidences of angiolyphatic, perineurial invasion and lymph node metastasis. Chronic gastritis was found 91.2% associated with the tumor. Atrophic change with chronic gastritis was found in age group of >=60 years. No significant statistical difference in comparing between macroscopic types and microscopic cell types of tumor with atrophic change. Intestinal metaplasia was found more common in male of age >=60 years at both body and antrum with the most common of type I (intestinal type). No different incidence of Helicobacter pylori infection in male and female or age groups was found. Helicobacter pylori were found most commonly in both body and antrum with evidence of glanditis and lymphoid aggregation. No significant statistical difference in comparing between macroscopic types and microscopic cell types of tumor with incidence of intestinal metaplasia of Helicobacter pylori infection was found. Conclusion : The pattern and distribution of the advanced gastric carcinoma in Thailand found to be the same as the national behavior of usual gastric carcinoma. The current hypothesis of gastric cancer in this country is believed to follow by the high incidence of gastritisÂ with high H. pyloriÂ infection. Atrophic change and intestinal metaplasia may be blocked or prevented by dietary factors of excessive fresh fruits, vegetables and low salt intake. Thus, H. pylori is not insufficient to give rise to gastric carcinoma but many other cofactors or predisposing conditions must play a role in the etiology and pathogenesis of gastric carcinoma in Thailand.